2017
DOI: 10.1519/jsc.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variation in Male Youth Athletes' Countermovement Jump After Plyometric Training: A Meta-Analysis of Controlled Trials

Abstract: Moran, J, Sandercock, GRH, Ramírez-Campillo, R, Meylan, CMP, Collison, J, and Parry, DA. Age-related variation in male youth athletes' countermovement jump after plyometric training: A meta-analysis of controlled trials. J Strength Cond Res 31(2): 552-565, 2017-Recent debate on the trainability of youths has focused on the existence of periods of accelerated adaptation to training. Accordingly, the purpose of this meta-analysis was to identify the age- and maturation-related pattern of adaptive responses to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
4
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(183 citation statements)
references
References 71 publications
7
161
4
2
Order By: Relevance
“…Interestingly, a previous meta‐analysis has demonstrated similar effects from PLY regardless of age, physical activity, and athletic experience . In contrast to those findings, Moran et al showed age‐related variation in the response to PLY in youth male athletes.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Interestingly, a previous meta‐analysis has demonstrated similar effects from PLY regardless of age, physical activity, and athletic experience . In contrast to those findings, Moran et al showed age‐related variation in the response to PLY in youth male athletes.…”
Section: Discussionmentioning
confidence: 92%
“…One limitation of the existing reviews summarizing the effects of PLY is that they do not include the large number of original studies that have been published recently . Some recent reviews have been published, but these investigated non‐performance outcomes such as bone health, bone mineral density, or the age‐related variation in the effects of PLY . Others have investigated the effects of PLY on performance of only single outcomes and/or have been devoted to specific subgroups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review used the same methodology as a recent meta-analysis on plyometric training in male youth athletes [47] and was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [28]. The study was approved by the university's institutional review board.…”
Section: Protocolmentioning
confidence: 99%